Transient and Steady Sliding Friction of Elastomers: Impact of Vertical Lift - Nakano, Ken; Kono, Masaharu (Frontiers in Mechanical Engineering, 2020)
The sliding friction of elastomers has been investigated numerically and theoretically for the line contact between a cylindrical rigid indenter and a “frictionless” Kelvin-Voigt foundation. The onset of sliding under an abrupt increase in the drive velocity has been simulated with different boundary conditions of the rigid indenter. When the rigid indenter is not allowed to move in any directions, just an abrupt change in the friction force appears, which is not accompanied by any transient processes. However, when the rigid indenter is able to move in the vertical direction, the transient sliding friction including three different time constants appears, resembling the typical transition from the static friction to the kinetic friction, in spite of no static friction considered in the simulation. The above drastic difference is caused by the “vertical lift” of the rigid indenter, which is induced by the damping of the Kelvin-Voigt foundation. Besides, the vertical lift affects strongly on the characteristics of the steady sliding friction, which is explained well by using the critical velocity determined from the asymptotes in the master curve of friction coefficient.